METODE-METODE DALAM PENYELIDIKAN DALAM PSIKOLOGI PERKEMBANGAN: METODE-METODE DALAM PENYELIDIKAN DALAM PSIKOLOGI PERKEMBANGAN - Urik Taurik; Nelmi Hafizah Mokoginta; Frezy Paputungan (LPPM UNiversitas Bina Mandiri Gorontalo, 2023)
To deeply understand human development, In conducting investigations in developmental psychology, there are several methods that can be used. in developmental psychology, it is important to choose the right method according to the purpose of the study. Research in the field of developmental psychology is essential to understanding human change and development from childhood to adulthood.In this journal, we will discuss methods of inquiry in developmental psychology. Methods of inquiry in developmental psychology have an important role to play in building a solid understanding of critical aspects of human development, such as cognition, socialization, emotions, and morality. These methods allow researchers to collect accurate empirical data, analyze it, and draw useful conclusions. By understanding and applying these methods effectively, developmental psychologists can further their understanding of the complexities of human development and make significant contributions to the development of relevant theories and interventions. These methods include introspective methods, extrospective methods, biographical methods, longitudinal methods, and cross-sectional methods. Each method has its own advantages and disadvantages, so it is necessary to choose the right method according to the research objectives and the characteristics of the individuals being studied. Developmental psychologists often spend time investigating and observing developmental processes occurring under normal circumstances. The aim of this paper is to provide a better understanding of investigative methods in developmental psychology and how these methods can be used to understand behavior change. and mental processes that occur in humans from infancy to adulthood.